Can MRI Visual Assessment Differentiate the Variants of Primary-Progressive Aphasia? - Sajjadi, S.A.; Sheikh-Bahaei, N.; Cross, J.; Gillard, J.H.; Scoffings, D.; Nestor, P.J. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Primary-progressive aphasia is a clinically and pathologically heterogeneous condition. Nonfluent, semantic, and logopenic are the currently recognized clinical variants. The recommendations for the classification of primary-progressive aphasia have advocated variant-specific patterns of atrophy. The aims of the present study were to evaluate the sensitivity and specificity of the proposed imaging criteria and to assess the intra- and interrater reporting agreements.MATERIALS AND METHODS: The cohort comprised 51 patients with a root diagnosis of primary-progressive aphasia, 25 patients with typical Alzheimer disease, and 26 matched control participants. Group-level analysis (voxel-based morphometry) confirmed the proposed atrophy patterns for the 3 syndromes. The individual T1-weighted anatomic images were reported by 3 senior neuroradiologists.RESULTS: We observed a dichotomized pattern of high sensitivity (92%) and specificity (93%) for the proposed atrophy pattern of semantic-variant primary-progressive aphasia and low sensitivity (21% for nonfluent-variant primary-progressive aphasia and 43% for logopenic-variant primary-progressive aphasia) but high specificity (91% for nonfluent-variant primary-progressive aphasia and 95% for logopenic-variant primary-progressive aphasia) in other primary-progressive aphasia variants and Alzheimer disease (sensitivity 43%, specificity 92%). MR imaging was least sensitive for the diagnosis of nonfluent-variant primary-progressive aphasia. Intrarater agreement analysis showed mean κ values above the widely accepted threshold of 0.6 (mean, 0.63 ± 0.16). Pair-wise interobserver agreement outcomes, however, were well below this threshold in 5 of the 6 possible interrater contrasts (mean, 0.41 ± 0.09).CONCLUSIONS: While the group-level results were in precise agreement with the recommendations, semantic-variant primary-progressive aphasia was the only subtype for which the proposed recommendations were both sensitive and specific at an individual level.ADAlzheimer diseaselvPPAlogopenic-variant PPAnfvPPAnonfluent-variant PPAPPAprimary-progressive aphasiasvPPAsemantic-variant PPA